Quercetin’s effects on intestinal polyp multiplicity and macrophage number in the Apc(Min/+) mouse - Murphy, E.A. (2011)
Numerous in vitro studies argue for quercetin’s chemopreventive potential in colon cancer; however experimental studies in rodents are limited. Macrophages play a role in tumorigenesis, but the effects of quercetin on macrophage infiltration in colon cancer is unknown. We examined the effects of quercetin on intestinal polyp multiplicity and macrophage number in Apc(Min/+) mice. Apc(Min/+) mice were assigned to placebo or quercetin (n=8/group) groups. Mice were given a placebo or quercetin (0.02%) diet from 4–20 wks of age after which intestines were analyzed for polyp number and size in the small intestine (sections 1–4) and colon (section 5) and for macrophage number in the small intestine (section 1 and 3). Spleen weight was determined as a marker of systemic inflammation. Quercetin decreased total intestinal polyps by 67% (p<0.05). Specifically, quercetin reduced intestinal polyps in categories >2 mm (69%) and 1–2 mm (79%) (P<0.05), and in sections 2 (75%), 3 (80%) and 4 (79%) (P<0.05). Quercetin also decreased macrophage number in sections 1 (57%) and 3 (81%), and spleen weight (P<0.05). These data suggest that quercetin can reduce polyp number and size distribution in the Apc(Min/+) mouse and that these effects may be related to a reduction in macrophage infiltration.